2022
DOI: 10.1128/spectrum.02622-22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of “ Candidatus Liberibacter asiaticus” Based on Four Hypervariable Genomic Regions in China

Abstract: The hypervariable genomic regions derived from 35 published C Las genomes were used to decipher the genetic diversity of C Las strains and identify 10 new strains with high variations in prophage regions. Characterizing these variations in the C Las bacteria might provide insight into their evolution and adaptation to host plants and insects in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Furthermore, the reduced genetic diversity (Pi = 0.00005 ± 0.00001) observed within populations may elucidate the absence of a distinct geographic pattern. Low genetic diversity indicates comparatively minor genetic distinctions among individuals within the population, potentially attributable to genetic drift or other influencing factors [27,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the reduced genetic diversity (Pi = 0.00005 ± 0.00001) observed within populations may elucidate the absence of a distinct geographic pattern. Low genetic diversity indicates comparatively minor genetic distinctions among individuals within the population, potentially attributable to genetic drift or other influencing factors [27,62].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study utilized four hypervariable genomic regions to examine the genetic diversity of CLas in the Fujian and Guangxi provinces of China. Notably, the results indicated that the genetic diversity of CLas appeared to be unaffected by geographical location, citrus varieties, and HLB symptoms [27]. Nevertheless, these studies do not provide comprehensive information on the epidemiology and distribution of HLB in other regions of mainland China, and there is limited knowledge about the demographic history.…”
Section: Introductionmentioning
confidence: 94%
“…The outcomes indicate that the spectral response of trees affected by HLB was greater than that of unaffected trees in the nearinfrared red, and green spectral bands. Gao et al (2022), stated that the disease, commonly referred to as HLB has spread throughout areas that cultivate citrus fruits, including Guangxi, Guangdong, and Fujian. Fourie et al (2021) stated that HLB has yet to be detected in the southern African region.…”
Section: Figure 1hlb-infected Tree With Symptoms Of Blotchy Mottling ...mentioning
confidence: 99%
“…Here, we compare genomic diversity among six species of the Liberibacter genus using publicly available and assembled genome sequences. We are not the first to compare the genome content in Liberibacter species ( Thapa et al, 2020 ; Gao et al, 2022 ). For example, Thapa et al (2020) recently studied a sample of 37 Liberibacter genomes to investigate systematic relationships and genetic diversity within species.…”
Section: Introductionmentioning
confidence: 99%